Molecular Subtype and Mutational Profile of Endometrial Atypical Hyperplasia/Endometrioid Intraepithelial Neoplasia - Leino, Annamari; Nostolahti, Anton; Ahtikoski, Anne; Huvila, Jutta (Ovid Technologies (Wolters Kluwer Health), 2026)
Endometrial atypical hyperplasia/endometrioid intraepithelial neoplasia (EAH/EIN) is the acknowledged precursor of most endometrial carcinomas. Our aim was to assess the molecular alterations and the 4 specific molecular subtypes in EAH/EIN diagnosed on endometrial biopsy. Forty EAH/EIN biopsies were stained for estrogen receptor (ER), mismatch repair (MMR) proteins (PMS2 and MSH6), and p53 and were subjected to genomic testing (NGS Panel, Canexia Health V5). Based on these results, cases were assigned to 1 of 4 molecular subtypes [POLEmut, MMRd, p53abn, and no specific molecular profile (NSMP)]. Follow-up data was collected. There was 1 POLEmut case with a pathogenic POLE mutation (P286R), 5 were MMRd, 1 was p53abn, and the remaining 33 were NSMP. Thirty-nine of 40 cases harbored one or several mutations known to be associated with endometrial carcinoma pathogenesis (PIK3CA, PTEN, and CTNNB1). On follow-up, there was carcinoma or EAH identified in a subsequent hysterectomy or biopsy in 6 of 6 patients with MMRd or p53abn EAH, compared with 19 of 34 with NSMP or POLEmut (P = 0.067). Most EAH/ EIN (33/40, 81.5%) are of the NSMP molecular subtype. Molecular subtypes other than NSMP (eg, POLE mutation, MMR deficiency, and p53 mutant pattern staining) are present in EAH/ EIN but are less common than in carcinoma. Mutations associated with EC pathogenesis were identified in 39/40 (97.5%) biopsies containing EAH/EIN, highlighting the neoplastic nature of this lesion and raising the possibility of using sequencing (NGS) as an adjuvant test to support a diagnosis of EAH/EIN.